2021
DOI: 10.1021/acs.est.0c05925
|View full text |Cite
|
Sign up to set email alerts
|

A Searchable Database for Prediction of Emission Compositions from Upstream Oil and Gas Sources

Abstract: Atmospheric emissions from oil and gas production operations are composed of multiple hydrocarbons and can have large variations in composition. Accurate estimates of emission compositions are needed to estimate the fate and impacts of emissions and to attribute emissions to sources. This work presents a database, constructed with empirical data and thermodynamic models, that can be queried to estimate hydrocarbon compositions from emission sources present at oil and gas production sites. The database can be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Past research demonstrates that C 2 H 6 :CH 4 ratios found in fossil fuel extraction, processing, and transportation operations are highly variable (Cardoso‐Saldaña et al., 2021; Peischl et al., 2018; Roest & Schade, 2017; Roscioli et al., 2015; Smith et al., 2015). Our findings confirm these highly variable C 2 H 6 :CH 4 source ratios in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research demonstrates that C 2 H 6 :CH 4 ratios found in fossil fuel extraction, processing, and transportation operations are highly variable (Cardoso‐Saldaña et al., 2021; Peischl et al., 2018; Roest & Schade, 2017; Roscioli et al., 2015; Smith et al., 2015). Our findings confirm these highly variable C 2 H 6 :CH 4 source ratios in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Fossil natural gas is primarily CH 4 , but contains other hydrocarbons such as ethane (C 2 H 6 ) at various mixing ratios that depend both on fossil deposit composition and downstream processing procedures (Cardoso‐Saldaña et al., 2019, 2021). The ratio of C 2 H 6 :CH 4 is therefore useful for the attribution of different individual natural gas sources such as well heads, compressor stations, storage tanks, coal bed off‐gassing etc.…”
Section: Introductionmentioning
confidence: 99%